Experiences of nurses educated outside the European Union of a Swedish bridging program and the program's role in their integration into the nursing profession: a qualitative interview study - Emina Hadziabdic; Anna-Maria Sarstrand Marekovic; Johanna Salomonsson; Kristiina Heikkilä (BMC, 2021)
Abstract Background Countries all over the world are experiencing a shortage of registered nurses (RNs). Therefore, some countries, including Sweden, have tried to solve this by recruiting internationally educated nurses (IENs). Countries offer bridging programs as educational support to qualify IENs for nursing work in the destination country. However, there is little research on IENs' experiences of bridging programs in European countries and how these programs facilitate their integration into the world of work and their new society. The aim of this study is to explore the experiences of nurses, originally educated outside the EU (European Union)/EES, of the Swedish bridging program and of the program's role in facilitating their integration into the nursing profession in Sweden. Methods A qualitative descriptive design was used to explore the topic based on 11 informants' perspectives and experiences. Purposive sampling was used to recruit participants at one university in Sweden. Data were collected by individual interviews using a semi- structured interview guide during the year 2019 and were analysed using an interpretative thematic approach. Results Two main themes emerged from the analysis: 1) Return to nursing, and 2) The bridging program as a tool for transition to nursing in Sweden. The first theme includes conditions and experiences such as personal motivation and determination, and support from others that the participants described as important in order to achieve the goal of re-establishing themselves as registered nurses in Sweden. Furthermore, the second theme describes the participants' experiences of the bridging program as mostly positive because it led to new learning and achievements that were valuable for the transition to nursing in Sweden; however, the participants also emphasised the challenges of their transition into the nursing profession, which were related to instances of misrecognition of their professional competence and the uncertain outcome of the program. Conclusions This study found that the bridging program facilitated integration into the nursing profession for nurses educated outside the EU/EES, especially knowledge gained in clinical-based training. Thus, it is important to recognise and value the IENs' experience and previous knowledge and training when developing the bridging program's curriculum.